Age Related Change of Total Length of Fallopian Tubes in Bangladesh Female Cadaver - Hena, Hasna; Ara, Shamim; Ullah, Md Enayet; Qasim, Rubina; Siddiqua, Dilruba; Jahora, Fatema (Update Dental College Journal, 2013)
Context: Human life begins in the fallopian tube. It receives the oocyte from the ovary and fertilization take place here. It provides nourishment for the fertilized ovum and transports it to the uterus. So the Fallopian tube is one of the vital organs for human fertility. In treatment of infertility (in ART) and in the management of ectopic (tubal) pregnancies, the knowledge of the anatomy of the fallopian tube is necessary. Study Design: Descriptive type of study.Place & period of study: Department of Anatomy, Dhaka Medical College, Dhaka from July 2008 to June 2009. Materials: 120 postmortem human fallopian tubes were collected from 60 unclaimed dead bodies that were under examination in the morgue of Department of Forensic Medicine, Dhaka Medical College, Dhaka. Methods: The samples were divided into three age groups: Group-A (10-13 years), Group-B (14-45 years) and Group-C (46-50 years). Results: In the present study, the mean (± SD) total length of the right and left Fallopian tubes were 9.60 ± 0.55 cm & 9.28 ± 0.48 cm in group A, 11.54 ± 0.80 cm & 11.28 ± 0.71 cm in Group B and 9.25 ± 0.26 cm & 9.10 ± 0.31 cm in Group C respectively. There was no significant difference between the mean length of right and left Fallopian tubes. The highest mean length was found in group B and lowest mean length was in group C. The difference in mean length of the Fallopian tube between Group A & Group B and Group B & Group C were statically significant (P < 0.001). Conclusion: In this study, it was observed that there was significant change in length of fallopian tubes in relation to age. DOI: http://dx.doi.org/10.3329/updcj.v1i2.13980 Update Dent. Coll. j. 2011: 1(2): 13-16